Pericarp development in fruit of epiphytic cacti: Implications for fruit classification and macro-morphology in the cactaceae - de Almeida, Odair José Garcia [UNESP]; de Souza, Luiz Antonio; Paoli, Adelita Aparecida Sartori [UNESP]; Davis, Arthur R.; Cota-Sánchez, J. Hugo (Canadian Science Publishing, 2018)
The family Cactaceae exhibits an assortment of fleshy and dry fruit types with various shapes dictated by the gynoecium outline and surrounding pericarpel. Consequently, conflicting terminology exists regarding cactus fruit classification because the fruit is a complex structure in which various floral parts participate in development. We examined fruit morphogenesis in four epiphytic cacti and provided a description of developmental events from post-anthesis to fruit maturation, which unveiled new structures valuable in fruit characterisation and taxonomy of the Hylocereeae and Rhipsalideae. Succinctly, the cactus fruit is a carpellar ovary embedded in a long-shoot (pericarpel). The pericarp originates from five components: internal ovarian epidermis that delimits the fruit locule, ovary (proper), collateral vascular bundles, pericarpel (receptacular origin), and external pericarpel epidermis. In addition, cell expansion and stored mucilage, a sticky substance involved in seed dispersal, occurs during fruit development. We propose the term cactidium, a complex fruit with accessory structures of pericarpellar origin surrounding the gynoecial boundary, to describe the cactus fruit. This term is appropriate because members of the Cactaceae bear unique traits, such as areoles in the reproductive structures (pericarpel), which may produce scale-leaves, bristles, and spines.
Keywords: Cactidium; Cactus fruit classification; Fruit morphology; Ontogeny; Pericarp